Erosion of Dosage Compensation Impacts Human iPSC Disease Modeling - Mekhoubad, Shila; Bock, Christoph; de Boer, A. Sophie; Kiskinis, Evangelos; Meissner, Alexander; Eggan, Kevin (Cell stem cell, 2012)
Although distinct human induced pluripotent stem cell (hiPSC) lines can display considerable epigenetic variation, it has been unclear whether such variability impacts their utility for disease modeling. Here, we show that although low-passage female hiPSCs retain the inactive X chromosome of the somatic cell they are derived from, over time in culture they undergo an “erosion” of X chromosome inactivation (XCI). This erosion of XCI is characterized by loss of XIST expression and foci of H3-K27-trimethylation, as well as transcriptional derepression of genes on the inactive X that cannot be reversed by either differentiation or further reprogramming. We specifically demonstrate that erosion of XCI has a significant impact on the use of female hiPSCs for modeling Lesch-Nyhan syndrome. However, our finding that most genes subject to XCI are derepressed by this erosion of XCI suggests that it should be a significant consideration when selecting hiPSC lines for modeling any disease. [Display omitted] ► hiPSCs can produce a robust model for the study of Lesch-Nyhan syndrome (LNS) ► Female hiPSCs undergo transcriptional derepression of the inactive X (Xi) ► As derepression of Xi occurs, the LNS phenotype in female carrier lines is lost ► Erosion of dosage compensation effects most X-linked loci in female hiPSC and hESC lines